Clickable SBA-15 mesoporous materials: synthesis, characterization and their reaction with alkynes - Malvi, Bharmana; Sarkar, Bibhas R.; Pati, Debasis; Mathew, Renny; Ajithkumar, Thalasseril G.; Sen Gupta, Sayam (Journal of Materials Chemistry, 2009)
SBA-15 mesoporous silica has been functionalized with azidopropyl groups through both one-pot co-condensation and post-synthetic grafting. For both these methodologies, azidopropyltriethoxysilane was used to introduce the azidopropyl groups. The azidopropyl modified SBA-15 material synthesized by one-pot co-condensation had hexagonal crystallographic order, pore diameters up of 50 angstrom, and the content of azidopropyl groups was found to be 1.3 mmol g(-1). The presence of the azidopropyl group was confirmed by multinuclear ((13)C, (29)Si) solid state NMR and IR spectroscopy. Both these materials underwent very efficient Cu(I)-catalyzed azide alkyne ``click'' reaction (CuAAC) with a variety of alkynes. Nearly 85% of the azide present in the SBA-15 material was converted to the corresponding triazole when propargyl alcohol was used as the substrate. This methodology was also used to incorporate mannose into SBA-15. Incubation of this mannose labeled SBA-15 with fluorescein labeled Concanavalin-A led to the formation of a fluorescent silica-protein hybrid material. The ease of synthesis for the azide labeled SBA-15 material together with its ability to undergo very efficient chemoselective CuAAC in water would make it a very attractive platform for the development of covalently anchored catalysts, enzymes and sensors.

Clicking molecular hooks on silica nanoparticles to immobilize catalytically important metal complexes: the case of gold catalyst immobilization - Ganai, Anal Kumar; Bhardwaj, Rima; Hotha, Srinivas; Sen Gupta, Sayam; Bhagavatula L. V. Prasad (New Journal of Chemistry, 2010)
Gold mediated reactions have emerged as one of the best choices for affecting a variety of chemical transformations with a wide range of functional group tolerance. Application of such transformations to industrial processes necessitates immobilization of the Au ions into a matrix for easy separation of the catalyst after reaction. We report the synthesis and characterization of silica nanoparticles in which Au(III) has been immobilized through a 1,2,3-triazole linkage using an alkynalated picolinic acid exploiting ``click chemistry''. The Au( III) immobilized silica nanoparticle has been thoroughly characterized using FT-IR, C-13 CP MAS NMR and XPS. The utility of these particles as an easily separable catalyst for the Hashmi phenol synthesis is also reported.

Synthesis and characterization of poly-L-lysine-grafted silica nanoparticles synthesized via NCA polymerization and click chemistry - Kar, Mrityunjov; Vijayakumar, P. S.; Bhagavatula L. V. Prasad; Sen Gupta, Sayam (Langmuir, 2010)
Polypeptide polymer-grafted silica nanoparticles are of considerable interest because the ordered secondary structure of the polypeptide grafts imparts novel functional properties onto the nanoparticle composite. The synthesis of poly-L-lysine-grafted nanoparticles would be of particular interest because the high density of cationic charges on the surface could lead to many applications such as gene delivery and antimicrobial agents. In this work, we have developed a ``grafting-to'' approach using a combination of NCA polymerization and ``click chemistry'' to synthesize poly-L-lysine-grafted silica nanoparticles with a high graft density of 1 chain/nm(2). The covalent attachment of poly-L-lysine to silica nanoparticles (PLL-silica) was confirmed using a variety of techniques such as C-13 CP MAS NMR, TGA, and IR. This methodology was then extended to graft poly-L-lysine-b-poly-L-leucine copolymer (PLL-b-PLLeu-silica) and poly-L-benzylglutamate (PLUG silica) onto silica nanoparticles. All of these polypeptide-grafted nanoparticles show interesting aggregation properties in solution. The efficacy of PLL-silica and PLL-h-PLLeu-silica as antimicrobial agents was tested on both gram-negative B. cull and grain-positive Bacillus subtilis.

Facile synthesis of unusual glycosyl carbamates and amino acid glycosides from propargyl 1,2-orthoesters as glycosyl donors - Shaikh, Ashif Y.; Sureshkumar, Gopalsamy; Pati, Debasish; Sen Gupta, Sayam; Hotha, Srinivas (Organic & Biomolecular Chemistry, 2011)
Propargyl 1,2-O-orthoesters are exploited for the synthesis of 1,2-trans O-glycosides of protected amino acids. N-Fmoc- and N-Cbz protected serine/threonine - benzyl/methyl esters reacted well with glucosyl-, galactosyl-, mannosyl- and lactosyl- derived propargyl 1,2-orthoesters affording respective 1,2-trans glycosides in good yields under AuBr(3)/4 angstrom MS Powder/CH(2)Cl(2)/rt. t-Boc serine derivative gave serine 1,2-orthoester and glycosyl carbamate. Optimized conditions enabled preparation of new glycosyl carbamates from N-Boc protected amines in a single step using gold catalysts and propargyl 1,2-orthoesters in excellent yields.

Fe(III) complex of biuret-amide based macrocyclic ligand as peroxidase enzyme mimic - Panda, Chakadola; Ghosh, Munmun; Panda, Tamas; Banerjee, Rahul; Sen Gupta, Sayam (Chemical Communications, 2011)
An Fe(III) complex of a biuret-amide based macrocyclic ligand that exhibits both excellent reactivity for the activation of H(2)O(2) and high stability, especially at low pH and high ionic strength, is reported.

Functionalization of SBA-15 mesoporous materials using ``thiol-ene click'' michael addition reaction - Kumari, Sushma; Malvi, Bharmana; Ganai, Anal Kumar; Pillai, Vijayamohanan K.; Sen Gupta, Sayam (Journal of Physical Chemistry C, 2011)
Methacrylate-labeled SBA-15 has been successfully synthesized from calcined SBA-15 and commercially available 3-trichlorosilyl propylmethacrylate. This material undergoes efficient thiol-ene ``click reaction'' with a variety of both thiol and disulfide-containing substrates in aqueous and organic media. The products were thoroughly characterized by a variety of analytical techniques including multinuclear (C-13, Si-29) solid-state NMR, TG-DTA, and nitrogen adsorption desorption studies. Disulfide-containing substrates in which the TCEP-mediated reduction of the disulfide bond and its subsequent addition to the methacrylate group anchored in SBA-15 in one-pot were used to synthesize a silica-protein hybrid material composed of biotin-labeled SBA-15 and streptavidin. Electrochemically active material was synthesized from the reaction of ferrocene-containing thiol and the methacrylate-labeled SBA-15. The ease of synthesis for the methacrylate-labeled SBA-15 material together with its ability to undergo efficient chemoselective thiol-ene reaction would make it a very attractive platform for the development of covalently anchored enzymes and sensors.

Gold catalyzed glycosidations for the synthesis of sugar acrylate/acrylamide hybrids and their utility - Thadke, Shivaji A.; Kar, Mritunjoy; Sen Gupta, Sayam; Hotha, Srinivas (Carbohydrate Research, 2011)
Propargyl glyco 1,2-orthoesters were exploited for the efficient synthesis of interesting glycomonomers such as glyco-acrylates and acrylamides using gold catalysts. It was observed that propargyl glyco 1,2-orthoesters with hydroxyethyl acrylates gives very good yield of the corresponding glyco-acrylates in a single step in the presence of catalytic amount of gold(III) catalyst; whereas, gold catalyzed glycosidation reaction on hydroxyethyl acrylamides was found to yield the corresponding acrylamidoyl 1,2-orthoester which was then converted to the corresponding glycol-acrylamide in the presence of catalytic amount of TMSOTf. Synthesized glyco-acrylate/acrylamide monomers are shown to undergo thiolate addition as well as free radical polymerization (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: carbohydrates; Glycoacrylamides; Glycoacrylates; Glycopolymers; glycosylation; Gold

Self-standing three-dimensional networks of nanoparticles with controllable morphology by dynamic templating of surfactant hexagonal domains - Sharma, Kamendra P.; Ganai, Anal Kumar; Sen Gupta, Sayam; Kumaraswamy, Guruswamy (Chemistry of Materials, 2011)
Assembly of nanoparticles into free-standing three-dimensional networks has implications for a wide range of applications. We show that dynamic templating of surfactant hexagonal domains is a facile technique to organize nanoparticles into a network of particulate strands. Dispersed particles (> 10 nm), independent of particle chemistry, assemble into networks, when the surfactant matrix cools into the hexagonal phase. We demonstrate assembly of inorganic, polymeric, and protein nanoparticles into networks. Where particle assembly is reversible, particles are coated with polymers that are subsequently cross-linked to stabilize the networks after surfactant removal. This technique involves near ambient temperatures and a benign water wash for template removal. The network mesh size can be varied from submicrometers to tens of micrometers by controlling the cooling rate. Particle networks can be flow-oriented prior to cross-linking, and interpenetrating networks can also be formed.
Keywords: hexagonal; macroporous; nanoparticle; self assembly; surfactant

Synthesis and characterization of poly-L-lysine grafted SBA-15 using NCA polymerization and click chemistry - Kar, Mrityunjoy; Malvi, Bharmana; Das, Anindita; Panneri, Suyana; Sen Gupta, Sayam (Journal of Materials Chemistry, 2011)
Poly-L-lysine (PLL) grafted ordered mesoporous material was prepared by a combination of NCA polymerization and click chemistry. Large pore SBA-15 with a mesopore diameter of similar to 12 nm was synthesized using a previously reported method. The surface of this SBA-15 material was modified with azidopropyl groups. This ``clickable'' SBA-15 was then reacted with an alkyne terminated poly-L-lysine synthesized by the ring-opening polymerization of 3-cbz-L-lysine NCA with N-TMS propargylamine as the initiator. This procedure allows grafting of a uniform polymer film with a high polymer loading. No appreciable pore blocking was observed upon grafting of PLL. No change in the periodic structure of the SBA-15 was observed throughout the grafting process. The SBA-15 PLL conjugate was characterized using (13)C and (29)Si NMR, XRD, FT-IR, N(2) adsorption-desorption and thermogravimetry. The results indicate that polypeptides can be easily grafted onto various ordered mesoporous materials by this ``grafting to'' methodology with accessible pores and high loadings of the polypeptide.

Synthesis of glycopolypeptides by the ring opening polymerization of O-glycosylated-alpha-amino acid N-carboxyanhydride (NCA) - Pati, Debasis; Shaikh, Ashif Y.; Hotha, Srinivas; Sen Gupta, Sayam (Polymer Chemistry, 2011)
The novel synthesis of O-glycosylated lysine-NCA from a stable glycosyl donor and a commercially available protected amino acid in very high yield is reported. These O-glycosylated lysine-NCA monomers underwent ring opening polymerization using simple primary amine initiators to form well defined, high molecular weight homoglycopolypeptides and diblock co-glycopolypeptides. The synthesis of azide labelled end functionalized glycopolypeptides and amphiphilic diblock copolypeptides is also reported. This methodology represents an easy and practical route to the synthesis of O-glycosylated polypeptides with 100% glycosylation.

Synthesis of poly-L-glutamic acid grafted silica nanoparticles and their assembly into macroporous structures - Kar, Mrityunjoy; Pauline, Minois; Sharma, Kamendra; Kumaraswamy, Guruswamy; Sen Gupta, Sayam (Langmuir, 2011)
Polypeptide-coated silica nanoparticles represent an interesting class of organic inorganic hybrids since the ordered secondary structure of the polypeptide grafts imparts functional properties to these nanoparticles. The synthesis of a poly-L-glutamic acid (PLGA) silica nanoparticle hybrid by employing N-carboxyanhydride (NCA) polymerization to synthesize the polypeptide chains and Cu catalyzed azide alkyne cycloaddition reaction to graft these chains onto the silica surface is reported. This methodology enables the synthesis of well-defined polypeptide chains that are attached onto the silica surface at high surface densities. The PLGA-silica conjugate particles are well dispersed in water, and have been thoroughly characterized using multinuclear (C-13, Si-29) solid state NMR, thermogravimetric analysis, Fourier transform infrared, dynamic light scattering, and transmission electron microscopy. The pH-dependent reversible aggregation of the PLGA-silica particles, driven by the change in PLGA structure, has also been studied. Preliminary results on the use of aqueous dispersions of silica-PLGA for the preparation of three-dimensional macroporous structures with oriented pores by ice templating methodology are also demonstrated. These macroporous materials, comprising a biocompatible polymer shell covalently attached to rigid inorganic cores, adopts an interesting lamellar structure with fishbone-type architecture.

Controlled synthesis of O-glycopolypeptide polymers and their molecular recognition by lectins - Pati, Debasis; Shaikh, Ashif Y.; Das, Soumen; Nareddy, Pavan Kumar; Swamy, Musti J.; Hotha, Srinivas; Sen Gupta, Sayam (Biomacromolecules, 2012)
The facile synthesis of high molecular weight water-soluble O-glycopolypeptide polymers by the ring-opening polymerization of their corresponding N-carboxyanhydride (NCA) in very high yield (overall yield > 70%) is reported. The per-acetylated-O-glycosylated lysine-NCA monomers, synthesized using stable glycosyl donors and a commercially available protected amino acid in very high yield, was polymerized using commercially available amine initiators. The synthesized water-soluble glycopolypeptides were found to be alpha-helical in aqueous solution. However, we were able to control the secondary conformation of the glycopolypeptides (alpha-helix vs nonhelical structures) by polymerizing raceznic amino acid glyco NCAs. We have also investigated the binding of the glycopolypeptide poly(alpha-manno-O-lys) with the lectin Con-A using precipitation and hemagglutination assays as well as by isothermal titration calorimetry (ITC). The ITC results clearly show that the binding process is enthalpy driven for both alpha-helical and nonhelical structures, with negative entropic contribution. Binding stoichiometry for the glycopolypeptide poly(alpha-manno-O-lys) having a nonhelical structure was slightly higher as compared to the corresponding polypeptide which adopted an alpha-helical structure.

Encapsulation of enzyme in large mesoporous material with small mesoporous windows - Malvi, Bharmana; Sen Gupta, Sayam (Chemical Communications, 2012)
Trypsin has been encapsulated in the mesopores of a hierarchical mesoporous silica material synthesized via Cu(I) catalyzed azide-alkyne click reaction between azide functionalized large spherical SBA-15 particles and alkyne functionalized mesoporous silica nanoparticles (MSNs). Encapsulated trypsin functions as an efficient biocatalyst and can be recycled several times.

Multiple topologies from glycopolypeptide-dendron conjugate self-assembly: nanorods, micelles, and organogels - Pati, Debasis; Kalva, Nagendra; Das, Soumen; Kumaraswamy, Guruswamy; Sen Gupta, Sayam; Ambade, Ashootosh V. (Journal of the American Chemical Society, 2012)
Glycopolypeptides (GPs) were synthesized by ring-opening polymerization of glycosylated N-carboxyanhydride monomer and attached to hydrophobic dendrons at one chain end by ``click'' reaction to obtain amphiphilic anisotropic macromolecules. We show that by varying polypeptide chain length and dendron generation, an organogel was obtained in dimethylsulfoxide, while nanorods and micellar aggregates were observed in aqueous solutions. Assemblies in water were characterized by electron microscopy and dye encapsulation. Secondary structure of the GP chain was shown to affect the morphology, whereas the chain length of the poly(ethylene glycol) linker between the GP and dendron did not alter rod-like assemblies. Bioactive surface chemistry of these assemblies displaying carbohydrate groups was demonstrated by interaction of mannose-functionalized nanorods with ConA.

One pot glucose detection by [Fe-III(biuret-amide)] immobilized on mesoporous silica nanoparticles: an efficient HRP mimic - Malvi, Bharmana; Panda, Chakadola; Dhar, Basab B.; Sen Gupta, Sayam (Chemical Communications, 2012)
An [Fe-III(biuret-amide)] complex has been immobilized onto mesoporous silica nanoparticles via Cu(I) catalyzed azide-alkyne click chemistry. This hybrid material functions as an efficient peroxidase mimic and was successfully used for the quantitative determination of hydrogen peroxide and glucose via a one-pot colorimetric assay.

Synthesis and self-assembly of glycopolypeptides - Pati, Debasis; Sen Gupta, Sayam (Abstracts of Papers of the American Chemical Society, 2012)

Synthesis of functional hybrid silica scaffolds with controllable hierarchical porosity by dynamic templating - Ganai, Anal Kumar; Kumari, Sushma; Sharma, Kamendra P.; Panda, Chakadola; Kumaraswamy, Guruswamy; Sen Gupta, Sayam (Chemical Communications, 2012)
We report a facile one-pot synthesis of hierarchically porous scaffolds, with independent control over nanoparticle mesoporosity and scaffold macroporosity. Our technique combines the chemistry of mesoporous silica nanoparticles with the control afforded by dynamic templating of surfactant mesophases. These materials are readily functionalizable and allow controllable spatial variation in macroporosity.

Synthesis of silk fibroin-glycopolypeptide conjugates and their recognition with lectin - Das, Soumen; Pati, Debasis; Tiwari, Neha; Nisal, Anuya; Sen Gupta, Sayam (Biomacromolecules, 2012)
Silk fibroin (SF), the natural fibrous protein created by the Bombyx mori silk worm, is being increasingly excellent mechanical strength, high oxygen/water permeability, excellent mechanical strength; high oxygen/water:permeability, and biocompatibility: :It is also well known that surface. modification of SF, With Organic ligands such as the extracellular protein :binding. Arg-Gly-Asp, (RGD) peptides:,: help adhesion and,proliferation. of cells better-a key; requirement for it to function as extracellular. matrices; In this, Work, We have conjugated synthetic glycopolypeptides (GPs) that were synthesized by controlled ring opening polymerization of alpha-manno-lys N-carboxyanhydrides (NCAs) onto SF by using Cu catalyzed click reaction to synthesize 1 a new hybrid :Material (SF GP), Which We believe will have :both the mechanical properties of native SF and the molecular recognition property of the carbohydrates in the GP. By controlling the :amount of GP grafted onto SF, we have made three SF GP conjugates that differ in their ability to assemble into films. SF GP conjugates having a very high content of GP formed completely water soluble brush like polymer that displayed very high affinity toward the lectin concanavalin-A (Con-A) Films cast from SF-GP conjugates using lower amounts of grafted GP were more stable in water, and the stability can be modulated by varying the amount of G grafted. The water insoluble film SF-GP(25) was also found to bind to fluorescently labeled Con A, as was seen by confocal microscopy Such SF-GP hybrid films may be useful as mimics of extracellular matrices for tissue engineering:

Catalytic signal amplification using [Fe-III(biuret-amide)]-mesoporous silica nanoparticles: visual cyanide detection - Panda, Chakadola; Dhar, Basab B.; Malvi, Bharmana; Bhattacharjee, Yudhajit; Sen Gupta, Sayam (Chemical Communications, 2013)
Catalytic signal amplification was used for the colorimetric detection of CN- in aqueous media by using the enzyme catalase in tandem with mesoporous silica nanoparticle based synthetic HRP enzyme mimic Fe-MSNs. Signal amplification up to a maximum of eight fold was observed for the reporter ``oxidized TMB'' with respect to the added CN- ion.

Development of a multifunctional catalyst for a ``relay'' reaction - Ganai, Anal Kumar; Shinde, Pravin; Dhar, Basab B.; Sen Gupta, Sayam; Bhagavatula L. V. Prasad (RSC Advances, 2013)
In the area of catalysis, nanoparticles and enzymes are two of the most important systems. By amalgamating the two, we present here proof of the concept that it is possible to prepare a multifunctional catalyst that can carry out a ``relay'' reaction. The catalyst consists of a surface bound enzyme on a metal(core)-silica(shell) nanoparticle architecture. Here the enzyme catalyzes the 1st reaction and the metal nanoparticles act as a catalyst for the 2nd reaction of the product from the 1st reaction. In particular, we have studied the catalytic activity of glucosidase grafted Au@mSiO(2) on 4-nitrophenyl-beta-glucopyranoside, where glucosidase will catalyse the 1st step to generate 4-nitrophenol, which acts as a substrate for the next reduction step which is catalysed by the Au nanoparticles present inside the mesoporous silica shell.

Large centimeter-sized macroporous ferritin gels as versatile nanoreactors - Kumari, Sushma; Kulkarni, Amol; Kumaraswamy, Guruswamy; Sen Gupta, Sayam (Chemistry of Materials, 2013)
Organized assemblies of bionanoparticles such as ferritin provides templates that can be exploited for nanotechnological applications. Organization of ferritin into well-defined three-dimensional assemblies is challenging and has attracted considerable attention recently. We have synthesized, for the first time, large (centimeter-sized) self-standing macroporous scaffold monoliths from ferritin bionanoparticles, using dynamic templating of surfactant H-1 domains. These scaffolds comprise three-dimensionally connected strands of ferritin, organized as a porous gel with porosity similar to 55 mu m. The iron oxide inside the ferritin scaffold can be easily replaced with catalytically active monodisperse zerovalent transition metal nanoparticles using a very simple protocol. Since the ferritin is cross-linked in the scaffold, it is significantly robust with enhanced thermal stability and better tolerance toward several organic solvents in Comparison to the native ferritin bionanoparticle. In addition, the scaffold macropores facilitate substrate and reagent transport and hence the monoliths containing active Pd or iron oxide nanoparticles inside apo-ferritin bionanoparticles were used as a recyclable heterogeneous catalyst for the oxidation of 2,3,6-trimethyl phenol to 2,3,6-trimethyl-1,4-benzoquinone (precursor for Vitamin E synthesis) and for Suzuki-Miyaura cross-coupling reaction in both aqueous and organic solvents. The protein shell around the nanoparticles protects them from agglomeration, a phenomenon that otherwise plagues nanoparticles-based catalysis. The presence of macropores allow the ferritin scaffold to act as catalytic monolith for continuous flow reactions having rapid reaction rates, while offering a low pressure drop. Finally, the Pd@apo-ferritin scaffold was immobilized inside a steel cartridge and used for the continuous flow hydrogenation of alkenes to their corresponding alkanes for 15 cycles without any loss of activity.
Keywords: catalysis; continuous flow; ferritin; gel; macroporous materials; Self-assembly

Poly-L-arginine grafted silica mesoporous nanoparticles for enhanced cellular uptake and their application in DNA delivery and controlled drug release - Kar, Mrityunjoy; Tiwari, Neha; Tiwari, Mitali; Lahiri, Mayurika; Sen Gupta, Sayam (Particle & Particle Systems Characterization, 2013)
Mesoporous silica nanoparticles (MSNs), that are capable of delivering gene and drugs to organisms in an effective and selective way have attracted much attention lately for its potential in the treatment of cancer. However, the successful application of MSNs for delivery of plasmid DNA or drugs requires surface modification of the silica with positively charged functional groups so that it binds to the negatively charged nucleic acids and also helps it penetrate through the cell membrane. We report for the first time the synthesis of a hybrid MSN where the cell penetrating cationic polypeptide poly-L-arginine synthesized by NCA polymerization is grafted onto the external surface of MSN using click chemistry. These poly-L-arginine grafted MSNs show low cytotoxity (85% cell viability at 100 g/mL MSN concentration) and high cellular uptake by both HeLa and A549 (>90%). The poly-L-arginine grafted MSNs were used effectively to deliver mCherry DNA plasmid into cells leading to expression of the protein mCherry inside the cells (transfection efficiency 60%). In contrast, poly-L-arginine grafted non-porous silica nanoparticles were unable to express the protein mCherry inside the cells although their uptake into the cells was as efficient as with poly-L-arginine grafted MSNs. We also show preliminary results to demonstrate that these hybrid MSNs can be used as a delivery vehicle for the anticancer drug Doxorubicin towards cancerous cells HeLa and A549. The biocompatibility of poly-L-arginine and its cell penetrating ability are expected to make these MSN conjugates very useful carriers for the delivery of genes and drugs into cancer cells.

Synthesis and self-assembly of amphiphilic homoglycopolypeptide - Dhaware, Vinita; Shaikh, Ashif Y.; Kar, Mrityunjoy; Hotha, Srinivas; Sen Gupta, Sayam (Langmuir, 2013)
The synthesis of the amphiphilic homoglycopolypeptide was carried out by a combination of NCA polymerization and click chemistry to yield a well-defined Polypeptide having an amphiphilic carbohydrate on its side chain. The amphiphilicity of the carbohydrate was achieved by incorporation of an alkyl chain, at the C-6 position of the carbohydrate thus also rendering the homoglycopolypeptide amphiphilic. The homoglycopolypeptide formed multimicellar aggregates in water above a critical concentration of 0.9 mu M due to phase separation. The multimicellar aggregates were characterized by DLS, TEM, and AFM. It is proposed that hydrophobic interactions of the aliphatic chains at the 6-position of the sugar moieties drives the assembly of these rod-like homoglycopolypeptide into large;spherical aggregates. These multimicellar aggregates encapsulate both hydrophilic as well as hydrophobic dye as was confirmed by confocal microscopy. finally, amphiphilic random polypeptides containing 10% and 20% alpha-D-mannose in addition to glucose containing a, hydrophobic alkyl chain at its 6 position were synthesized by our methodology, and these polymers Were also found to assemble into spherical nanostructures. The spherical assemblies Of amphiphilic random glycopolypeptides containing 10% and 20% mannose were found to be surface bioactive and were found, to interact with the lectin Con-A.

Synthesis of end-functionalized phosphate and phosphonate-polypeptides by ring-opening polymerization of their corresponding N-carboxyanhydride - Das, Soumen; Kar, Mrityunjoy; Sen Gupta, Sayam (Polymer Chemistry, 2013)
Phosphopolypeptides provide an interesting biomimetic analog for phosphorylated proteins that are involved in biomineralization. We have developed a high yielding synthesis of cysteine-based phosphate and phosphonate N-carboxyanhydride (NCA) by using the thiol-ene coupling reaction. These phosphate and phosphonate NCA monomers underwent polymerization using simple primary amine initiators to form well defined homophosphopolypeptides. Using a bifunctional initiator we were able to install a ``clickable'' alkyne or azide group at the end of the polypeptide chain. We were also able to successfully synthesize fully water-soluble phosphonate based polypeptides by hydrolysis of the corresponding phosphonate ester groups in the polypeptide. These water-soluble phosphopolypeptides adopt a random coil conformation at physiological pH.

Cationic charged helical glycopolypeptide using ring opening polymerization of 6-deoxy-6-azido-glyco-N-carboxyanhydride - Shaikh, Ashif Y.; Das, Soumen; Pati, Debasis; Dhaware, Vinita; Sen Gupta, Sayam; Hotha, Srinivas (Biomacromolecules, 2014)
Glycopolypeptides with a defined secondary structure are of significance in understanding biological phenomena. Synthetic glycopolypeptides, or polypeptides featuring pendant carbohydrate moieties, have been of particular interest in the field of tissue engineering and drug delivery. In this work, we have synthesized charged water-soluble glycopolypeptides that adopt a helical conformation in water. This was carried out by the synthesis of a glyco-N-carboxyanhydride (glyco-NCA) containing an azide group at the sixth position of the carbohydrate ring. Subsequently, the NCA was polymerized to obtain azide-containing glycopolypeptides having good control over molecular weight and polydispersity index (PDI) in high yields. We were also able to control the incorporation of the azide group by synthesizing random co-glycopolypeptide containing 6-deoxy-6-azido and regular 6-OAc functionalized glucose. This azide functionality allows for the easy attachment of a bioactive group, which could potentially enhance the biological activity of the glycopolypeptide. We were able to obtain water-soluble charged glycopolypeptides by both reducing the azide groups into amines and using CuAAC with propargylamine. These charged glycopolypeptides were shown to have a helical conformation in water. Preliminary studies showed that these charged glycopolypeptides showed good biocompatibility and were efficiently taken up by HepG2 cells.

Fe-TAML encapsulated inside mesoporous silica nanoparticles as peroxidase mimic: femtomolar protein detection - Kumari, Sushma; Dhar, Basab B.; Panda, Chakadola; Meena, Abhishek; Sen Gupta, Sayam (ACS Applied Materials & Interfaces, 2014)
Peroxidase, such as horseradish peroxidase (HRP), conjugated to antibodies are routinely used for the detection of proteins via an ELISA type assay in which a critical step is the catalytic signal amplification by the enzyme to generate a detectable signal. Synthesis of functional mimics of peroxidase enzyme that display catalytic activity which far exceeds the native enzyme is extremely important for the precise and accurate determination of very low quantities of proteins (fM and lower) that is necessary for early clinical diagnosis. Despite great advancements, analyzing proteins of very low abundance colorimetrically, a method that is most sought after since it requires no equipment for the analysis, still faces great challenges. Most reported HRP mimics that show catalytic activity greater than native enzyme (similar to 40-fold) are based on metal/metal-oxide nanoparticles such as Fe3O4. In this paper, we describe a second generation hybrid material developed by us in which approximately 25 000 alkyne tagged biuret modified Fetetraamido macrocyclic ligand (Fe-TAML), a very powerful small molecule synthetic HRP mimic, was covalently attached inside a 40 nm mesoporous silica nanopartide (MSN). Biuret-modified Fe-TAMLs represent one of the best small molecule functional mimics of the enzyme HRP with reaction rates in water close to the native enzyme and operational stability (pH, ionic strength) far exceeding the natural enzyme. The catalytic activity of this hybrid material is around 1000-fold higher than that of natural HRP and 100-fold higher than that of most metal/metal oxide nanoparticle based HRP mimics reported to date. We also show that using antibody conjugates of this hybrid material it is possible to detect and, most importantly, quantify femtomolar quantities of proteins colorimetrically in an ELISA type assay. This represents at least 10-fold higher sensitivity than other colorimetric protein assays that have been reported using metal/metal oxide nanoparticles as HRP mimic. Using a human IgG expressing cell line, we were able to demonstrate that the protein of interest human IgG could be detected from a mixture of interfering proteins in our assay.
Keywords: colorimetrically; immuno assay; MSN; peroxidase mimic; signal amplification

Formation of a room temperature stable Fe-V(O) complex: reactivity toward unactivated C-H bonds - Ghosh, Munmun; Singh, Kundan K.; Panda, Chakadola; Weitz, Andrew; Hendrich, Michael P.; Collins, Terrence J.; Dhar, Basab B.; Sen Gupta, Sayam (Journal of American Chemical Society, 2014)
An Fe-V(O) complex has been synthesized from equimolar solutions of (Et4N)(2)[Fe-III(Cl)(biuretamide)] and mCPBA in CH3CN at room temperature. The Fe-V(O) complex has been characterized by UV-vis, EPR, Mossbauer, and HRMS and shown to be capable of oxidizing a series of alkanes having C-H bond dissociation energies ranging from 99.3 kcal mol(-1) (cyclohexane) to 84.5 kcal mori (cumene). Linearity in the Bell-Evans-Polayni graph and the finding of a large kinetic isotope effect suggest that hydrogen abstraction is engaged the rate-determining step.

Investigation of C-C bond formation mediated by bombyx mori silk fibroin materials - Kuehbeck, Dennis; Ghosh, Munmun; Sen Gupta, Sayam; Diaz, David Diaz (ACS Sustainable Chemistry & Engineering, 2014)
The formation of C-C bonds is a prerequisite for all life on earth. Understanding the role of proteins in mediating the formation of these bonds is important for understanding biological mechanisms in evolution, as well as for designing ``green catalysts''. In this work, the ability of silk fibroin (SF) proteins to mediate selective C-C bond formation under mild conditions was comprehensively evaluated and compared between different SF-based materials and other proteins. Aqueous SF solution (ASFS), freeze-dried SF (FDSF), mesoporous SF (MPSF), and SF hydrogel (SFHG) materials were prepared and characterized by a variety of techniques including, among others, FE-SEM, ICP-OES, FT-IR, and TGA. The nitroaldol (Henry) reaction, Knoevenagel condensation, and direct aldol reaction were used as models for this study, in which the recovery and reusability of the protein was also evaluated.
Keywords: Aldol-like reactions; C-C Bond formation; Knoevenagel condensation; Proteins; Silk fibroin

Soft colloidal scaffolds capable of elastic recovery after large compressive strains - Rajamanickam, Raja; Kumar, Sushma; Kumar, Deepak; Ghosh, Shankar; Kim, Jong Chul; Tae, Giyoong; Sen Gupta, Sayam; Kumaraswamy, Guruswamy (Chemistry of Materials, 2014)
Assemblies of inorganic or glassy particles are typically brittle and cannot sustain even moderate deformations. This restricts the use of such materials to applications where they do not experience significant loading or deformation. Here, we demonstrate a general strategy to create centimeter-size macroporous monoliths, composed primarily (>90 wt %) of colloidal particles, that recover elastically after compression to about one-tenth their original size. We employ ice templating of an aqueous dispersion of particles, polymer, and cross-linker such that cross-linking happens in the frozen state. This method yields elastic composite scaffolds for starting materials ranging from nanoparticles to micron-sized dispersions of inorganics or glassy lattices. The mechanical response of the monoliths is also qualitatively independent of polymer type, molecular weight, and even cross-linking chemistry. Our results suggest that the monolith mechanical properties arise from the formation of a unique hybrid microstructure, generated by cross-linking the polymer during ice templating. Particles that comprise the scaffold walls are connected by a cross-linked polymeric mesh. This microstructure results in soft monoliths, with moduli similar to O (10(4) Pa), despite the very high particle content in their walls. A remarkable consequence of this microstructure is that the monolith mechanical response is entropic in origin: the modulus of these scaffolds increases with temperature over a range of 140 K. We show that interparticle connections formed by cross-linking during ice templating determine the monolith modulus and also allow relative motion between connected particles, resulting in entropic elasticity.

Uptake of Azo dyes into silk glands for production of colored silk cocoons using a green feeding approach - Nisal, Anuya; Trivedy, Kanika; Mohammad, Hasan; Panneri, Suyana; Sen Gupta, Sayam; Lele, Ashish K.; Manchala, Ramesh; Kumar, Nirmal S.; Gadgil, Mugdha; Khandelwal, Harish B.; More, Snehal; Laxman, Ryali Seeta (ACS Sustainable Chemistry & Engineering, 2014)
Dyeing of textile fabrics is considered to be one of the most polluting industries today, and there is a need to develop green processes that can reduce this pollution. A promising technology that can potentially cleanup the dyeing of silk fibers that are widely used for textile applications would involve the generation of intrinsically colored silk cocoons. This can be achieved by feeding of Bombyx mori silkworm larvae with a modified feed of mulberry leaves containing a sprayed dye solution. This process significantly reduces the need for treating toxic dye effluents that are generated in traditional dyeing processes. In this report, we have evaluated a set of seven different azo dyes that are used in the textile industry for dyeing to produce intrinsically dyed silk. The dyes used in the study had similar chemical structures with systematically varying partition coefficients. The results suggest that while some dyes produced intrinsically colored silk other did not. Careful evaluation of the physical properties of these related azo dyes suggest that the balance of hydrophobic and hydrophilic character is necessary for diffusion of the dye from the alimentary canal of the silkworm larva into the hemolymph and later into the silk glands. The partition coefficient of the dye also determines the preferential association of the dye with either sericin or fibroin protein in the silkworm gland and finally into the cocoon. These insights are extremely important in development of novel dye molecules that can be successfully fed to Bombyx mori silkworm larvae for producing intrinsically colored silk of various colors and shades.
Keywords: Azo dyes; Biochemical pathways; Color silk; Dye uptake; `' Green `' silk

Bioactive polymersomes self-assembled from amphiphilic.PPO-glycopolypeptides: synthesis, characterization, and dual-dye encapsulation - Das, Soumen; Sharma, Dharmendar Kumar; Chakrabarty, Suman; Chowdhury, Arindam; Sen Gupta, Sayam (Langmuir, 2015)
Glycopolypeptide-based polymersomes have promising applications as vehicles for targeted drug delivery because they are capable of encapsulating different pharmaceuticals of diverse polarity as well as interacting with specific cell surfaces due to their hollow structural morphology and bioactive surfaces. We have synthesized glycopolypeptide-b-poly(propylene oxide) by ROP of glyco-N-carboxyanhydride (NCA) using the hydrophobic amine-terminated poly(propylene oxide) (PPO) as the initiator. This block copolymer is composed of an FDA-approved PPO hydrophobic block in conjugation with hydrophilic glycopolypeptides which are expected to be biocompatible. We demonstrate the formation of glycopolypeptide-based polymersomes from the self-assembly of glycopolypeptide-b-poly(propylene oxide) in which the presence of an ordered helical glycopolypeptide segment is required for their self-assembly into spherical nanoscale (similar to 50 nm) polymersomes. The polymersomes were characterized in detail using a variety of techniques such as TEM, AFM, cryo-SEM, and light-scattering measurements. As a model for drugs, both hydrophobic (RBOE) and hydrophilic (calcein) dyes have been incorporated within the polymersomes from solution. To substantiate the simultaneous entrapment of the two dyes, spectrally resolved fluorescence microscopy was performed on the glycopeptide polymersomes cast on a glass substrate. We show that it is possible to visualize individual nanoscale polymersomes and effectively probe the dyes colocalization and energy-transfer behaviors therein as well as investigate the variation in dual-dye encapsulation over a large number of single polymersomes. Finally, we show that the galactose moieties present on the surface can specifically recognize lectin RCA(120), which reveals that the polymersomes surface is indeed biologically active.

Mechanism of alcohol oxidation by Fe-V(O) at room temperature - Ghosh, Munmun; Nikhil, Y. L. K.; Dhar, Basab B.; Sen Gupta, Sayam (Inorganic Chemistry, 2015)
{Selective oxidation of alcohol to its corresponding carbonyl compound is an important chemical process in biological as well as industrial reactions, The heme containing enzyme CytP450 has been known to selectively oxidize akohols to their corresponding carbonyl compounds. The mechanism of this reaction, which involves high-valent Fe-IV(O)-porphyrin(center dot+) intermediate with alcohol, has been well-studied extensively both with the native enzyme and with model complexes. In this paper, we report for the first time the mechanistic insight of, alcohol oxidation with Fe-V(O) complex of biuret TAML (bTAML), Which is isoelectronic with Fe-IV(O)-porphyrin(center dot+) intermediate form in CytP450. The oxidations displayed saturation kinetics, which allowed us to determine both the binding constants and first-order rate constants for the reaction. The K and k values observed for thel oxidation of benzyl alcohol by Fe-V(O) at room temperature (K = 300 M-1

Mechanism of oxygen atom transfer from Fe-V(O) to olefins at room temperature - Singh, Kundan K.; Tiwari, Mrityunjay K.; Dhar, Basab B.; Vanka, Kumar; Sen Gupta, Sayam (Inorganic Chemistry, 2015)
In biological oxidations, the intermediate Fe-V(0)(OH) has been proposed to be the active species for catalyzing the epoxidation of alkenes by nonheme iron complexes. However, no study has been reported yet that elucidates the mechanism of direct O-atom transfer during the reaction of Fe-V(0) with alkenes to form the corresponding epoxide. For the first time, we study the mechanism of O-atom transfer to alkenes using the Fe-V(0) complex of biuret-modified Fe-TAML at room temperature. The second-order rate constant (k(2)) for the reaction of different alkenes with Fe-V(0) was determined under single-turnover conditions. An 8000-fold rate difference was found between electron-rich (4-methoxystyrene; k(2) = 216 M-1 s(-1)) and electron-deficient (methyl transcinnamate; k(2) = 0.03 M-1 s(-1)) substrates. This rate difference indicates the electrophilic character of Fe-V(0). The use of cis-stilbene as a mechanistic probe leads to the formation of both cis- and trans-stilbene epoxides (73:27). This suggests the formation of a radical intermediate, which would allow C-C bond rotation to yield both stereoisomers of stilbene-epoxide. Additionally, a Hammett rho value of -0.56 was obtained for the para-substituted styrene derivatives. Detailed DFT calculations show that the reaction proceeds via a two-step process through a doublet spin surface. Finally, using biuret-modified Fe-TAML as the catalyst and NaOCl as the oxidant under catalytic conditions epoxide was formed with modest yields and turnover numbers.

Molecular Fe-complex as a catalyst probe for in-gel visual detection of proteins via signal amplification - Kumari, Sushma; Panda, Chakadola; Mazumdar, Shyamalava; Sen Gupta, Sayam (Chemical Communications, 2015)
We report the use of a molecular peroxidase mimic biuret-Fe-TAML for chemoselective labeling of proteins and the subsequent visual detection (<0.1 pmoles) of the conjugate in a polyacrylamide gel by catalytic signal amplification. Use of this probe in activity based protein profiling (ABPP) of serine proteases is also demonstrated.

Reactivity and operational stability of N-Tailed TAMLs through kinetic studies of the catalyzed oxidation of orange II by H2O2: synthesis and x-ray structure of an N-Phenyl TAML - Warner, Genoa R.; Mills, Matthew R.; Enslin, Clarissa; Pattanayak, Shantanu; Panda, Chakadola; Panda, Tamas Kumar; Sen Gupta, Sayam; Ryabov, Alexander D.; Collins, Terrence J. (Chemistry A-European Journal, 2015)
{The catalytic activity of the N-tailed (biuret) TAML (tetraamido macrocyclic ligand) activators [Fe{4-XC6H3-1,2-(NCOCMe2NCO)(2)NR}Cl](2-) (3; N atoms in boldface are coordinated to the central iron atom; the same nomenclature is used in for compounds 1 and 2 below), [X
Keywords: Hydrogen peroxide; iron; kinetics; Oxidation; reaction mechanisms

Controlled synthesis of end-functionalized mannose-6-phosphate glycopolypeptides for lysosome targeting - Das, Soumen; Parekh, Nimisha; Mondal, Basudeb; Sen Gupta, Sayam (ACS Macro Letters, 2016)
The ubiquitous expression of the mannose-6-phosphate receptor on the majority of human cells makes it a valid target in the quest to deliver therapeutics selectively to the lysosome. In this work end-functionalized polyvalent mannose-6-phosphate glycopolypeptides (M6P-GPs) with high molecular weights (up to 22 kDa) have been synthesized via NCA polymerization. These synthetic M6P-GPs were found to display minimal toxicity to cells in vitro and show exceptional selectivity for trafficking into lysosomes in various cell lines. Comparison of the cellular uptake behavior of M6P-GP and the corresponding mannose-GP polymer reveals that incorporation of the phosphate moiety at the 6-position of mannose completely alters its trafficking behavior and becomes exclusively lysosome specific. We also demonstrate that trafficking of M6P-GPs in mammalian cells is likely associated with the CI-MPR receptor pathway.

Electrocatalytic water oxidation by a molecular cobalt complex through a high valent cobalt oxo intermediate - Das, Debasree; Pattanayak, Santanu; Singh, Kundan K.; Garai, Bikash; Sen Gupta, Sayam (Chemical Communications, 2016)
Biuret-modified tetraamidomacrocyclic cobalt complex [Co-III-bTAML]- is shown to catalyze electrochemical water oxidation at basic pH leading to the formation of O-2. Electrochemical and spectroscopic studies indicate a high valent cobalt oxo intermediate isoelectronic to Co-V(O) as the active oxidant. The kinetic isotope effect of 8.63 indicates an atom proton transfer mechanism.

Glycopolypeptide-grafted bioactive polyionic complex vesicles (PICsomes) and their specific polyvalent interactions - Pandey, Bhawana; Mahato, Jaladhar; Cotta, Karishma Berta; Das, Soumen; Sharma, Dharmendar Kumar; Sen Gupta, Sayam; Chowdhury, Arindam (ACS Omega, 2016)
Glycopolypeptide-based self-assembled nano-/microstructures with surface-tethered carbohydrates are excellent mimics of glycoproteins on the cell surface. To expand the broad repertoire of glycopolypeptide-based supramolecular soft structures such as polymersomes formed via self-assembly of amphiphilic polymers, we have developed a new class of polyionic complex vesicles (PICsomes) with glycopolypeptides grafted on the external surface. Oppositely charged hydrophilic block copolymers of glycopolypeptide(20)-b-poly-L-lysine(100) and PEG(2k)-b-poly-L-glutamate(100) [PEG = poly(ethylene glycol)] were synthesized using a combination of ring-opening polymerization of N-carboxyanhydrides and ``click'' chemistry. Under physiological conditions, the catiomer and aniomer self-assemble to form glycopolypeptide-conjugated PICsomes (GP-PICsomes) of micrometer dimensions. Electron and atomic force microscopy suggests a hollow morphology of the PICsomes, with inner aqueous pool (core) and peripheral PIC (shell) regions. Owing to their relatively large (similar to micrometers) size, the hollowness of the supramolecular structure could be established via fluorescence microscopy of single GP-PICsomes, both in solution and under dry conditions, using spatially distributed fluorescent probes. Furthermore, the dynamics of single PICsomes in solution could be imaged in real time, which also allowed us to test for multivalent interactions between PICsomes mediated by a carbohydrate (mannose)-binding protein (lectin, Con-A). The immediate association of several GP-PICsomes in the presence of Con-A and their eventual aggregation to form large insoluble aggregate clusters reveal that upon self-assembly carbohydrate moieties protrude on the outer surface which retains their biochemical activity. Challenge experiments with excess mannose reveal fast deaggregation of GP-PICsomes as opposed to that in the presence of excess galactose, which further establishes the specificity of lectin-mediated polyvalent interactions of the GP-PICsomes.

Omniphilic polymeric sponges by ice templating - Chatterjee, Soumyajyoti; Sen Gupta, Sayam; Kumaraswamy, Guruswamy (Chemistry of Materials, 2016)
Sponges that absorb a large quantity of solvent relative to their weight, independent of the solvent polarity, represent useful universal absorbents for laboratory and industrial spills. We report the preparation of macroporous polymer sponges by ice templating of polyethylenimine aqueous solutions and their cross-linking in the frozen state. The as-prepared monolith is hydrophilic and absorbs over 30 fold its weight in water. Modification of this sponge using valeroyl chloride renders it omniphilic; viz., a modified sponge absorbs over 10-fold its dry weight of either water or hexane. Modification using palmitoyl chloride that has a longer chain length results in the preparation of a hydrophobic sponge with a water contact angle around 130, which retains its oleophilicity underwater. The solvent absorbed in these sponges can be simply squeezed out, and the sponges are stable to several hundred cycles of compression. The large pore sizes of these sponges allow rapid absorption of even high viscosity solvents such as pump oil. Finally, we demonstrate that these sponges are also able to separate apolar oils that are emulsified in water using surfactants. These high porosity sponges with controllable solvophilicity represent inexpensive, high performance universal absorbents for general solvent spills.

Tunable nanocarrier morphologies from glycopolypeptide-based amphiphilic biocompatible star copolymers and their carbohydrate specific intracellular delivery - Pati, Debasis; Das, Soumen; Patil, Naganath G.; Parekh, Nimisha; Anjum, Dalaver H.; Dhaware, Vinita; Ambade, Ashootosh V.; Sen Gupta, Sayam (Biomacromolecules, 2016)
Nanocarriers with carbohydrates on the surface represent a very interesting class of drug-delivery vehicles because carbohydrates are involved in biomolecular recognition events in vivo. We have synthesized biocompatible miktoarm star copolymers comprising glycopolypeptide and poly(e-caprolactone) chains using ring-opening polymerization and ``click chemistry''. The amphiphilic copolymers were self-assembled in water into morphologies such as nanorods, polymersomes, and micelles with carbohydrates displayed on the surface. We demonstrate that the formation of nanostructure could be tuned by chain length of the blocks and was not affected by the type of sugar residue. These nanostructures were characterized in detail using a variety of techniques such as TEM, AFM, cryogenic electron microscopy, spectrally resolved fluorescence imaging, and dye encapsulation techniques. We show that it is possible to sequester both hydrophobic as well as hydrophilic dyes within the nanostructures. Finally, we show that these noncytotoxic mannosylated rods and polymersomes were selectively and efficiently taken up by MDA-MB-231 breast cancer cells, demonstrating their potential as nanocarriers for drug delivery.

Versatile Cu-II metal-organic framework exhibiting high gas storage capacity with selectivity for CO2: conversion of CO2 to cyclic carbonate and other catalytic abilities - De, Dinesh; Pal, Tapan K.; Neogi, Subhadip; Senthilkumar, S.; Das, Debasree; Sen Gupta, Sayam; Bharadwaj, Parimal K. (Chemistry-A European Journal, 2016)
A linear tetracarboxylic acid ligand, H4L, with a pendent amine moiety solvothermally forms two isostructural metal-organic frameworks (MOFs) L-M (M=Zn-II, Cu-II). Framework L-Cu can also be obtained from L-Zn by post- synthetic metathesis without losing crystallinity. Compared with L-Zn, the L-Cu framework exhibits high thermal stability and allows removal of guest solvent and metal-bound water molecules to afford the highly porous, L-Cu. At 77K, L-Cu absorbs 2.57wt% of H-2 at 1bar, which increases significantly to 4.67wt% at 36bar. The framework absorbs substantially high amounts of methane (238.38cm(3)g(-1), 17.03wt%) at 303K and 60bar. The CH4 absorption at 303K gives a total volumetric capacity of 166cm(3)(STP)cm(-3) at 35bar (223.25cm(3)g(-1), 15.95wt%). Interestingly, the NH2 groups in the linker, which decorate the channel surface, allow a remarkable 39.0wt% of CO2 to be absorbed at 1bar and 273K, which comes within the dominion of the most famous MOFs for CO2 absorption. Also, L-Cu shows pronounced selectivity for CO2 absorption over CH4, N-2, and H-2 at 273K. The absorbed CO2 can be converted to value-added cyclic carbonates under relatively mild reaction conditions (20bar, 120 degrees C). Finally, L-Cu is found to be an excellent heterogeneous catalyst in regioselective 1,3-dipolar cycloaddition reactions (click reactions) and provides an efficient, economic route for the one-pot synthesis of structurally divergent propargylamines through three-component coupling of alkynes, amines, and aldehydes.
Keywords: click reactions; CO2 absorption; cyclic carbonate; heterogeneous catalysis; metal-organic frameworks

Amphi-functional mesoporous silica nanoparticles for dye separation - Shinde, Pravin; Sen Gupta, Sayam; Singh, Baljeet; Polshettiwar, Vivek; Prasad, Bhagavatula L. V. (Journal of Materials Chemistry A, 2017)
Synthesis of amphi-functional mesoporous silica nanoparticles (similar to 80 nm) by stepwise chemical modifications of outer and inner pore surfaces is reported. These materials display a clear "Janus" like character and are able to selectively and completely separate hydrophobic dyes form a mixture of dyes. Our results clearly suggest a clear partition of more hydrophobic dyes into the pores from a mixture of two dyes. In addition this material displays a remarkable recycling ability for 10 cycles with up to similar to 99% dye removal from water.

Catalytic macroporous biohydrogels made of ferritin-encapsulated gold nanoparticles - Kumari, Sushma; Haring, Marleen; Sen Gupta, Sayam; Diaz, David Diaz (Chempluschem, 2017)
Reported is a modular approach for the incorporation and stabilization of gold nanoparticles inside a three-dimensional macroporous hydrogel made of ferritin. The strategy, which involves the dynamic templating of surfactant H-1 domains, demineralization, and remineralization helps to overcome aggregation and degradation issues usually associated with bare-metal-based nanocatalysts. The catalytic activity of the so-synthesized bionanocomposite hydrogel was demonstrated in both nitroaldol (Henry) and nitroreduction model reactions in aqueous solution at room temperature. An interesting synergistic effect between basic residues of the protein and the gold nanoparticles was found in the nitroaldol reaction when carried out in water in the presence of a phase-transfer catalyst. Furthermore, the reduction of 4-nitrophenol and 4-nitroaniline catalyzed by the nanocomposite scaffold in the presence of NaBH4 proceeded significantly faster than that using other known Au- and Ag-based catalysts under similar conditions.

Electrochemical formation of Fe-V (O) and mechanism of its reaction with water during O-O bond formation - Pattanayak, Santanu; Chowdhury, Debarati Roy; Garai, Bikash; Singh, Kundan K.; Paul, Amit; Dhar, Basab B.; Sen Gupta, Sayam (Chemistry-A European Journal, 2017)
A detailed electrochemical investigation of a series of iron complexes (biuret-modified tetraamido iron macrocycles FeIII-bTAML), including the first electrochemical generation of Fe-V(O), and demonstration of their efficacy as homogeneous catalysts for electrochemical water oxidation (WO) in aqueous medium are reported. Spectroelectrochemical and mass spectral studies indicated FeV(O) as the active oxidant, formed due to two redox transitions, which were assigned as Fe-IV(O)/Fe-III(OH2)and Fe-V(O)/Fe-IV(O). The spectral properties of both of these high-valent iron oxo species perfectly match those of their chemically synthesised versions, which were thoroughly characterised by several spectroscopic techniques. The O-O bond-formation step occurs by nucleophilic attack of H2O on FeV(O). A kinetic isotope effect of 3.2 indicates an atom-proton transfer (APT) mechanism. The reaction of chemically synthesised Fe-V(O) in CH3CN and water was directly probed by electrochemistry and was found to be first-order in water. The pK(a) value of the buffer base plays a critical role in the rate-determining step by increasing the reaction rate several-fold. The electronic effect on redox potential, WO rates, and onset overpotential was studied by employing a series of iron complexes. The catalytic activity was enhanced by the presence of electron-withdrawing groups on the bTAML framework. Changing the substituents from OMe to NO2 resulted in an eightfold increase in reaction rate, while the overpotential increased threefold.

Iron complex catalyzed selective C-H bond oxidation with broad substrate scope - Jana, Sandipan; Ghosh, Munmun; Ambule, Mayur; Sen Gupta, Sayam (Organic Letters, 2017)
The use of a peroxidase-mimicking Fe complex has been reported on the basis of the biuret-modified TAML macrocyclic ligand 'framework (Fe-bTAML) as a catalyst to perform selective oxidation of unactivated 3 degrees C-H bonds and activated 2 degrees C-H bonds with low catalyst loading (1 mol %) and high product yield (excellent mass balance) under near neutral conditions and broad substrate scope (18 substrates which includes arenes, heteroaromatics, and polar functional groups). Aliphatic C-H oxidation of 3 and 2 sites of complex substrates was achieved with predictable selectivity using steric, electronic, and stereoelectronic rules that govern site selectivity, which included oxidation of (+)-artemisinin to (+)-10 beta-hydroxyartemisinin. Mechanistic studies indicate Fe-V(O) to be the active oxidant during these reactions.

Reductive activation of O-2 by a bioinspired Fe complex for catalytic epoxidation reactions - Singh, Kundan K.; Sen Gupta, Sayam (Chemical Communications, 2017)
Aerobic epoxidation of olefins catalyzed by iron complexes without the use of a sacrificial coreductant is unknown. We report the reductive activation of O-2 by a bioinspired [(bTAML)Fe-III(H2O)](-) (1) complex to catalyze the epoxidation of alkenes with TONs of up to 80. Spectroscopic and kinetic evidence indicates the involvement of FeV(O) as the active oxidant during the reaction.

Spectroscopic and reactivity comparisons of a pair of bTAML complexes with Fe-V=O and Fe-IV=O units - Pattanayak, Santanu; Jasniewsk, Andrew J.; Rana, Atanu; Draksharapu, Apparao; Singh, Kundan K.; Weitz, Andrew; Hendrich, Michael; Que, Lawrence, Jr.; Dey, Abhishek; Sen Gupta, Sayam (Inorganic Chemistry, 2017)
In this report we compare the geometric and electronic structures and reactivities of [Fe-V(O)](-) and [Fe-IV(O)](2-) species supported by the same ancillary nonheme biuret tetraamido macrocyclic ligand (bTAML). Resonance Raman studies show that the Fe-O vibration of the [Fe-IV(O)](2-) complex 2 is at 798 cm(-1), compared to 862 cm(-1) for the corresponding [Fe-V(O)](-) species 3, a 64 cm(-1) frequency difference reasonably reproduced by density functional theory calculations. These values are, respectively, the lowest and the highest frequencies observed thus far for nonheme high-valent Fe-O complexes. Extended X-ray absorption fine structure analysis of 3 reveals an Fe-O bond length of 1.59 angstrom, which is 0.05 angstrom shorter than that found in complex 2. The redox potentials of 2 and 3 are 0.44 V (measured at pH 12) and 1.19 V (measured at pH 7) versus normal hydrogen electrode, respectively, corresponding to the [Fe-IV(O)](2-)/[Fe-III(OH)](2-) and [Fe-V(O)](-)/[Fe-IV(O)](2-) couples. Consistent with its higher potential (even after correcting for the pH difference), 3 oxidizes benzyl alcohol at pH 7 with a second-order rate constant that is 2500-fold bigger than that for 2 at pH 12. Furthermore, 2 exhibits a classical kinteic isotope effect (KIE) of 3 in the oxidation of benzyl alcohol to benzaldehyde versus a nonclassical KIE of 12 for 3, emphasizing the reactivity differences between 2 and 3.

What drives the H-abstraction reaction in bio-mimetic oxoiron-bTAML complexes? A computational investigation - Mukherjee, Anagh (Physical Chemistry and Chemical Physics, 2018)
Monomeric iron-oxo units have been confirmed as intermediates involved in the C–H bond activation in various metallo-enzymes. Biomimetic oxoiron complexes of the biuret modified tetra-amido macrocyclic ligand (bTAML) have been demonstrated to oxidize a wide variety of unactivated C–H bonds. In the current work, density functional theory (DFT) has been employed to investigate the hydrogen abstraction (HAT) reactivity differences across a series of bTAML complexes. The cause for the differences in the HAT energy barriers has been found to be the relative changes in the energy of the frontier molecular orbitals (FMOs) induced by electronic perturbation.

Biopolymer/glycopolypeptide-blended scaffolds: synthesis, characterization and cellular interactions - Dhaware, Vinita; Diaz, David Diaz; Sen Gupta, Sayam (Chemistry-An Asian Journal, 2019)
Three-dimensional (3D) scaffolds formed from natural biopolymers gelatin and chitosan that are chemically modified by galactose have shown improved hepatocyte adhesion, spheroid geometry and functions of the hepatocytes. Galactose specifically binds to the hepatocytes via the asialoglycoprotein receptor (ASGPR) and an increase in galactose density further improves the hepatocyte proliferation and functions. In this work, we aimed to increase the galactose density within the biopolymeric scaffold by physically blending the biopolymers chitosan and gelatin with an amphiphlic beta-galactose polypeptide (PPO-GP). PPO-GP, is a di-block copolymer with PPO and beta-galactose polypeptide, exhibits lower critical solution temperature and is entrapped within the scaffold through hydrophobic interactions. The uniform distribution of PPO-GP within the scaffold was confirmed by fluorescence microscopy. SEM and mechanical testing of the hybrid scaffolds indicated pore size, inter connectivity and compression modulus similar to the scaffolds made from 100 % biopolymer. The presence of the PPO-GP on the surface of the scaffold was tested monitoring the interaction of an analogous mannose containing PPO-GP scaffold and the mannose binding lectin Con-A. In vitro cell culture experiments with HepG2 cells were performed on GLN-GP and CTS-GP and their cellular response was compared with GLN and CTS scaffolds for a period of seven days. Within three days of culture the Hep G2 cells formed multicellular spheroids on GLN-GP and CTS-GP more efficiently than on the GLN and CTS scaffolds. The multicellular spheroids were also found to infiltrate more in GLN-GP and CTS-GP scaffolds and able to maintain their round morphology as observed by live/dead and SEM imaging.
Keywords: adhesion; Aggregates; Cellular infiltration; Spheroids

Amphiphilic mannose-6-phosphate glycopolypeptide-based bioactive and responsive self-assembled nanostructures for controlled and targeted lysosomal cargo delivery - Mondal, Basudeb; Pandey, Bhawana; Parekh, Nimisha; Panda, Sidharth; Dutta, Tahiti; Padhy, Abinash; Sen Gupta, Sayam (Biomaterials Science, 2020)
Receptors of carbohydrate mannose-6-phosphate (M6P) are overexpressed in specific cancer cells (such as breast cancer) and are also involved in the trafficking of mannose-6-phosphate labeled proteins exclusively onto lysosomes via cell surface M6P receptor (CI-MPR) mediated endocytosis. Herein, for the first time, mannose-6-phosphate glycopolypeptide ((M6P)GP)-based bioactive and stimuli-responsive nanocarriers are reported. They are selectively taken up via receptor-mediated endocytosis, and trafficked to lysosomes where they are subsequently degraded by pH or enzymes, leading to the release of the cargo inside the lysosomes. Two different amphiphilic M6P block copolymers (M6P)GP(15)-(PPO44)-P-A and (M6P)GP(15)-(PCL25)(2) were synthesized by click reaction of the alkyne end-functionalized (M6P)GP(15) with pH-responsive biocompatible azide end-functionalized acetal PPO and azide end-functionalized branched PCL, respectively. In water, the amphiphilic M6P-glycopolypeptide block copolymers self-assembled into micellar nanostructures, as was evidenced by DLS, TEM, AFM, and fluorescence spectroscopy techniques. These micellar systems were competent to encapsulate the hydrophobic dye rhodamine-B-octadecyl ester, which was used as the model drug. They were stable at physiological pH but were found to disassemble at acidic pH (for (M6P)GP(15)-(PPO44)-P-A) or in the presence of esterase (for (M6P)GP(15)-(PCL25)(2)). These (M6P)GP based micellar nanoparticles can selectively target lysosomes in cancerous cells such as MCF-7 and MDA-MB-231. Finally, we demonstrate the clathrin-mediated endocytic pathway of the native FL-(M6P)GP polymer and RBOE loaded (M6P)GP micellar-nanocarriers, and selective trafficking of MCF-7 and MDA-MB-231 breast cancer cell lysosomes, demonstrating their potential applicability toward receptor-mediated lysosomal cargo delivery.

Synthesis of phospho-polypeptides via phosphate-containing N-carboxyanhydride: application in enzyme-induced self-assembly, and calcium carbonate mineralization - Mondal, Basudeb; Das, Soumen; Panda, Sidharth; Dutta, Tahiti; Sen Gupta, Sayam (ChemPlusChem, 2020)
An easy synthetic strategy was developed to synthesize the phosphate-functionalized amino acid N-carboxyanhydride (NCA), using simple primary amine initiators to obtain homo and block phospho-polypeptides with controlled molecular weight and molecular weight distribution. The methodology was extended to the synthesis of the end-functionalized homo polypeptides (15 to 50 repeat unit) and block co-polypeptides with PEG (0.7 K, 2 K, and 5 K) and glycopolypeptide (15-unit mannose glycopolypeptide) as one of the blocks. The deprotected fully water-soluble anionic phosphate-based polypeptides showed pH-dependent helical conformation with a helical content of 20 %, which further changed to beta-sheets upon addition of the enzyme alkaline phosphatase (ALP) due to dephosphorylation. The block co-polypeptide containing PEG as one of the blocks led to its self-assembly into colloidal structures, such as vesicles with a hydrodynamic diameter of similar to 250 nm, due to the formation of amphiphilic block co-polymer upon dephosphorylation. The nature of the colloidal structures formed can be temporally controlled by the extent of dephosphorylation. Finally, the phospho-polypeptides serve as a template for the mineralization of calcium carbonate with varying polymorphs and morphologies.
Keywords: Biomineralization; enzymes; phosphopolypeptides; Proteins; Self-assembly

Heterogeneous C-H functionalization in water via porous covalent organic framework nanofilms: a case of catalytic sphere transmutation - Sasmal, Himadri Sekhar; Bag, Saikat; Chandra, Bittu; Majumder, Poulami; Kuiry, Himangshu; Karak, Suvendu; Sen Gupta, Sayam; Banerjee, Rahul (Journal of the American Chemical Society, 2021)
Heterogeneous catalysis in water has not been explored beyond certain advantages such as recyclability and recovery of the catalysts from the reaction medium. Moreover, poor yield, extremely low selectivity, and active catalytic site deactivation further underrate the heterogeneous catalysis in water. Considering these facts, we have designed and synthesized solution-dispersible porous covalent organic framework (COF) nanospheres. We have used their distinctive morphology and dispersibility to functionalize unactivated C-H bonds of alkanes heterogeneously with high catalytic yield (42-99%) and enhanced regioand stereoselectivity (3 degrees:2 degrees = 105:1 for adamantane). Further, the fabrication of catalyst-immobilized COF nanofilms via covalent self-assembly of catalytic COF nanospheres for the first time has become the key toward converting the catalytically inactive homogeneous catalysts into active and effective heterogeneous catalysts operating in water. This unique covalent self-assembly occurs through the protrusion of the fibers at the interface of two nanospheres, transmuting the catalytic spheres into films without any leaching of catalyst molecules. The catalyst-immobilized porous COF nanofilms' chemical functionality and hydrophobic environment stabilize the high-valent transient active oxoiron(V) intermediate in water and restricts the active catalytic site's deactivation. These COF nanofilms functionalize the unactivated C-H bonds in water with a high catalytic yield (45-99%) and with a high degree of selectivity (cis:trans = 155:1; 3 degrees:2 degrees = 257:1, for cis-1,2-dimethylcyclohexane). To establish this approach's ``practical implementation'', we conducted the catalysis inflow (TON = 424 +/- 5) using catalyst-immobilized COF nanofilms fabricated on a macroporous polymeric support.

Electrocatalytic alcohol oxidation by a molecular iron complex - Kuiry, Himangshu; Das, Debasree; Das, Soumadip; Chakraborty, Soham; Chandra, Bittu; Sen Gupta, Sayam (Faraday Discussions, 2022)
An efficient electrochemical method for the selective oxidation of alcohols to their corresponding aldehydes/ketones using a biomimetic iron complex, [(bTAML)Fe-III-OH2](-), as the redox mediator in an undivided electrochemical cell with inexpensive carbon and nickel electrodes using water as an oxygen source is reported. The substrate scope also includes alcohols that contain O and N heteroatoms in the scaffold, which are well tolerated under these reaction conditions. Mechanistic studies show the involvement of a high-valent Fe-V(O) species, [(bTAML)Fe-V(O)](-), formed via PCET (overall 2H(+)/2e(-)) from [(bTAML)Fe-III-OH2](-) at 0.77 V (vs. Fc(+)/Fc). Moreover, electrokinetic studies of the oxidation of C-H bonds indicate a second-order reaction, with the C-H abstraction by Fe-V(O) being the rate-determining step. The overall mechanism, studied using linear free energy relationships and radical clocks, indicates a ``net hydride'' transfer, leading to the oxidation of the alcohol to the corresponding aldehyde or ketone. When the reaction was carried out at pH > 11, the reaction could be carried out at a similar to 500 mV lower potential than that at pH 8, albeit with reduced reaction rates. The reactive intermediate involved at pH > 11 is the corresponding one-electron oxidized [(bTAML)Fe-IV(O)](2-) species.

Solvent-free hydroxylation of unactivated C-H bonds in small molecules and macromolecules by a Fe complex - Chatterjee, Debasmita; Sajeevan, Amritha; Jana, Sandipan; Birajdar, Rajkumar S.; Chikkali, Samir H.; Sivaram, Swaminathan; Sen Gupta, Sayam (ACS CATALYSIS, 2024)
Keywords: Ball milling; solid-state C-H hydroxylation

Shola: a 3D porous hydrophobic-oleophilic lignocellulosic material for efficient oil/water separation - Mondal, Keya; Advani, Kushagra; Ghosh, Snigdha; Shanmugnathan, Kadhiravan; Kulsi, Goutam; Sivaram, Swaminathan; Sen Gupta, Sayam (Journal of Materials Chemistry A, 2025)
Transitioning from the fossil fuel era to a sustainable future requires increasing adoption of high-performing renewable materials in industrial applications. Natural polymers derived from lignocellulosic materials are often considered more environmentally friendly than their petroleum-based synthetic analogs. Aeschynomene aspera, commonly known as Shola, has been found to be a large source of amorphous cellulose and a useful sorbent for the removal of oil from water. The Shola pith, the pure white inner stem, is rich in cellulose and has an exquisite three-dimensional and hierarchical porous architecture created by nature. The pith consists of about 70 wt% cellulose as the main chemical component, which is much higher than what is found in other lignocellulosic sources. In addition, the pith has about 12 wt% hemicellulose, 2-3 wt% pectin, 10 wt% lignin, 2.5 wt% wax, and 2 wt% protein as other chemical components. It was observed that water has a high contact angle (135 degrees) on the surface of the pith, while oil droplets instantly spread on the surface, indicating excellent hydrophobic-oleophilic properties. Further studies reveal that the Shola pith exhibits a fast and high sorption capacity of 40-60 g/g for various oils and organic liquids. Silicone oil shows a sorption capacity of about 166 g/g. When applied to oil-floating-over-water, the Shola pith exhibits high selectivity for oil over water; almost all oil on the surface could be removed, leaving no trace of oil on the water surface. The Shola pith can also efficiently separate oil from an oil-in-water emulsion. This behavior is unprecedented in natural sorbents. The used material sorbs a considerable volume of the oil even after the 7th cycle. Furthermore about 95% of sorbed oil could be recovered from the material by solvent extraction. This study reveals for the first time some of the unique and interesting properties of Shola, a widely found biomass native to the eastern parts of the Indian subcontinent, and opens up possibilities of exploiting it for valuable applications.

Chirality transfer from covalent organic framework nanotubes to covalent organic framework films via chirality induction crystallization - Bag, Saikat; Chatterjee, Debasmita; Mahapatra, Rohan; Sasmal, Himadri Sekhar; Khatua, Arindam; Giri, Madhurima; Paul, Satyadip; Shelke, Ankita; Almasoud, Najla; Alomar, Taghrid S.; Ajithkumar, Thalasseril G.; Sen Gupta, Sayam; et al. (Advanced Materials, 2026)
We report the synthesis of homochiral crystalline covalent organic framework (COF) films that combine rigidity and porosity, offering significant promise for heterogeneous asymmetric catalysis. We prepared enantiopure COF films from achiral diamine and trialdehyde precursors using a chiral induction crystallization strategy. A Schiff-base reaction, catalyzed by a chiral acid, namely (R)- and (S)-camphorsulfonic acids (CSA) generated a beta-ketoenamine backbone with induced chirality. (R)- and (S)-camphorsulfonic acids direct the diamine-trialdehyde condensation and induce chirality during the nucleation of COF nanotubes, enabling their periodic arrangement and the formation of homochiral thin films. We successfully synthesized six distinct COF films with three different backbone functionalities: R-, S-TpAzo; R-, S-TpDPP; and R-, S-TpBDMe2, using the two enantiomers of the chiral camphorsulfonic acids. All films displayed strong circular dichroism signals and pronounced Cotton effects, confirming their enhanced enantiopurity. Both R- and S-TpAzo films exhibited the highest crystallinity, long-range order, and permanent porosity, making them particularly well-suited for catalytic applications. To demonstrate their utility, we encapsulated a bioinspired catalyst, (Et4N)2[FeIII(Cl)bTAML], within the chiral channels of the R- and S-TpAzo films. The resulting composite created a robust heterogeneous catalytic platform for the asymmetric epoxidation of alkenes, achieving excellent activity and enantioselectivity under ambient conditions.
Keywords: chiral induction; covalent organic framework nanotube; covalent organic framework thin film; heterogeneous catalysis